(untitled) (Plant Tissue Culture and Biotechnology, 2011)
Leaves, one year old stems and buds were used as explants. WPM, B5, MS, half and one-fourth strength MS with 2,4-?D, NAA, IBA, IAA and picloram 2, 5 and 10 mg/l were used for callus induction. Investigation into the seasonal effect on callus regeneration and explants browning was carried out in mid-April until September. Results showed that washing with sterile distilled water for one hour after surface sterilization was the best treatment for browning inhibition of explants than other treatments. Leaf explants have best callus formation. MS with 8 g/l agar had strong effect on callus formation. Culture for callus formation in May and June found to be higher than other months. 2,4-D, NAA and 10 mg/l picloram significantly enhanced callus formation. Leaf and bud explants sampling in April to May did not show any endophyte contamination but leaf explants in June until September, specially the one year old stems, showed intensive contamination. Key words: Seasonal effect, Browning inhibitor, Berberis vulgaris D. O. I. 10.3329/ptcb.v21i2.10239 Plant Tissue Cult. & Biotech. 21(2): 161-168, 2011 (December)